Relationship quality and relationship context as antecedents of person- and task-focused interpersonal citizenship behavior. - Settoon, Randall P.; Mossholder, Kevin W. (Journal of Applied Psychology, 2002)
A model hypothesizing relationship quality and relationship context as antecedents of two complementary forms of interpersonal citizenship behavior (ICB) was tested. Measures with coworkers as the frame of reference were used to collect data from 273 individuals working in 2 service-oriented organizations. As hypothesized, variables reflecting relationship quality were associated with person-focused ICB, as mediated by empathic concern. Also as hypothesized, a relationship context variable, network centrality, exhibited a direct relationship with task-focused ICB. Unexpectedly, network centrality was directly associated with person-focused ICB. and empathic concern was associated with task-focused ICB. The results are discussed, and implications for research and practice are offered.